More Than Meets the Eye: The Merging of Perceptual and Conceptual Knowledge in the Anterior Temporal Face Area - Collins, Jessica A.; Koski, Jessica E.; Olson, Ingrid R. (Frontiers in Human Neuroscience, 2016)
An emerging body of research has supported the existence of a small face sensitive region in the ventral anterior temporal lobe (ATL), referred to here as the “anterior temporal face area”. The contribution of this region in the greater face-processing network remains poorly understood. The goal of the present study was to test the relative sensitivity of this region to perceptual as well as conceptual information about people and objects. We contrasted the sensitivity of this region to that of two highly-studied face-sensitive regions, the fusiform face area and the occipital face area, as well as a control region in early visual cortex. Our findings revealed that multivoxel activity patterns in the anterior temporal face area contain information about facial identity, as well as conceptual attributes such as one’s occupation. The sensitivity of this region to the conceptual attributes of people was greater than that of posterior face processing regions. In addition, the anterior temporal face area overlaps with voxels that contain information about the conceptual attributes of concrete objects, supporting a generalized role of the ventral ATLs in the identification and conceptual processing of multiple stimulus classes.1 Introduction Over a decade of neuroimaging work has characterized the neural basis of face perception and identified several nodes that preferentially respond to faces relative to other objects (Haxby, Hoffman, & Gobbini, 2000; Nancy Kanwisher & Yovel, 2006). Most of this work has focused on the fusiform face area (FFA) and the occipital face area (OFA) (Kanwisher, McDermott, & Chun, 1997; Kanwisher & Yovel, 2006; Pitcher, Walsh, Yovel, & Duchaine, 2007), however an emerging literature has implicated an anterior temporal face area, on the ventral surface of the right anterior temporal lobes (vATLs) in or near perirhinal cortex, in facial processing (Avidan et al., 2013; Pinsk et al., 2009; Rajimehr, Young, & Tootell, 2009; Tsao, Moeller, & Freiwald, 2008). The function of the anterior temporal face area remains unclear. One body of research implicates this region in perception. Using single-cell recordings it has been shown that the identity of previously unfamiliar faces is represented in the population code of monkey vATL face